Reducing unassisted falls among admitted patients with cancer at NewYork-Presbyterian, Weill Cornell Medicine. Issue 28 (1st October 2022) - Garcia, Christine Ann; Rodriguez, German; Assalone, Dianna; DeBarbrie, Catherine; Taflin, Stefanie; Marsh, Kristen; Singh, Harjot Kaur; Lee, Jennifer Inhae; Crossman, Dan; Santacruz, Natan; McDonough, Jessica; DeJesus, Dana; et al.
Abstract : 353 Background: Patients with cancer are at particularly high risk for falls and may suffer worse morbidity and mortality, including fractures due to bony metastases, subsequent bleeding due to thrombocytopenia. In our tertiary NYC hospital in 2020, there were 67 falls among patients with cancer admitted to oncology floors, accounting for 12.4% of all WCM falls among 5% of admissions. In the first quarter of 2021, there were 15 total falls which triggered the oncology units to focus on falls' reduction efforts. Of the patients that fell during their inpatient admission during 2020, 20% of these patients were not considered "high risk for falls" based on the traditional Morse Falls' risk assessment, making it unclear if the traditional assessment can adequately risk stratify patients with cancer. Methods: Our SMART aim was to reduce the rate of unassisted inpatient falls per 1000 patient days (falls' rate) on oncology inpatient units (10N, 10S, 10C, 10W) at NewYork-Presbyterian, Weill Cornell Medicine by 10% from January 31, 2021- June 30, 2022. We initiated 5 iterative Plan-Do-Study-Act (PDSA) cycles on oncology units. Cycle 1 (2/2021) consisted of multidisciplinary root cause analysis meetings held with nurses, physicians, advanced practice providers, and environmental services. We also completed multipronged rapid cycle falls' audit among all oncology nurses. During cycle 2 (3/2021), new falls' signage was developed and posted outside each room and in patient bathrooms. During cycle 3 (6/2021), interdisciplinary falls' education was implemented. During cycle 4 (7/2021), a falls' prevention board was started to bring awareness to all team members. In cycle 5 (8/2021), a standardized, campus-wide post-fall huddle tool was implemented to deep dive into the "5 Whys" of falls. In cycle 6 (6/2022), we have just launched a prospective risk assessment tool to collect potential falls' risk factors not included in the Morse Falls' assessment. Results: From February 2021 to June 2022, we were able to significantly reduce our unassisted falls rate on oncology inpatient units by 57%, from 4.51 falls per 1000 patient days to 1.97 falls/1000 patient days. Variation in falls' rates over time shows a median rate of 2.3 falls per 1000 patient days from quarter in 2018 with a downward trend in 2021-2022. Conclusions: Through multiple PDSA cycles, we made iterative changes that ultimately reduced our unassisted falls rate among oncology patients. It was essential to engage key stakeholders including nurses, physicians, advance practice providers, patients and families in the discussion and get to the root of why patients were falling. Overall, this improved communication among team members and made the oncology units a safer place.